Stress State Evaluation by an Improved Support Vector Machine - Xin, L.; Zetao, Ch.; Yunpeng, Zh.; Jiali, X.; Shuicai, W.; Yanjun, Z. (Нейрофизиология, 2016)
Effective methods of evaluation of the psychological pressure can detect and assess realtime stress states, warning people to pay necessary attention to their health. This study is focused on the stress assessment issue using an improved support vector machine (SVM) algorithm on the base of surface electromyographic signals. After the samples were clustered, the cluster results were given to the loss function of the SVM to screen training samples. With the imbalance amongst the training samples after screening, a weight was given to the loss function to reduce the prediction tendentiousness of the classifier and, therefore, to decrease the error of the training sample and make up for the influence of the unbalanced samples. This improved the algorithm, increased the classification accuracy from 73.79% to 81.38%, and reduced the running time from 1973.1 to 540.2 sec. Experimental results show that this algorithm can help to effectively avoid the influence of individual differences on a stress appraisal effect and to reduce the computational complexity during the training phase of the classifier Ефективні методи визначення ступеня психологічного тиску можуть забезпечувати виявлення та оцінку стресових станів у реальному часі, примушуючи людей приділяти необхідну увагу їх здоров’ю. Метою нашого дослідження було оцінити стан стресу з використанням покращеного методу опорних векторів (SVM), базуючись на відведенні поверхневих електроміограм. Після того, як зразки даних були кластеризовані, результати передавалися до функції розділення SVM для того, щоб представити тренувальні зразки. Після встановлення дисбалансу між тренувальними зразками після скринінга для функції розділення надавався параметр ваги для зменшення тенденційності прогнозування класифікатора і, таким чином, зменшення похибки тренувального зразка і впливу незбалансованих зразків. Це покращувало алгоритм, підвищувало точність класифікації від 73.79 до 81.38 % та зменшувало час обробки від 1973.1 до 540.2 с. Результати експериментів показали, що даний алгоритм може допомогти ефективно уникнути впливу індивідуальних відмінностей на оцінювання стресу та зменшити складність комп’ютерних розрахунків у перебігу тренувальної фази діяльності класифікатора.